Costs and benefits of a mining project in Rönnbäck : a CBA on the social and environmental impacts of mining - Johansson, Kornelia (SLU/Dept. of Economics, 2017)
This study aims to give an overview of the costs and benefits from establishing a nickel mine in Rönnbäck, in the municipality of Storuman, Sweden. The mining industry is known to have both positive and negative effects on the society. The costs associated with the business include environmental disturbance and interest conflicts from local inhabitants and minority groups. The benefits from a mining project take its expression in terms of profit for the mining company, tax revenue and the creation of job opportunities. By using the transfer method and other CBA studies some of the impacts are examined. The result is a positive net social benefit with a value between 947 125 MSEK and 1 477 032 MSEK for the mining project which indicates that the project would have a beneficial impact on the society. It should be noted that only a few aspects are covered in this essay and that the case need further research.